Cortical Correlates of Impulsive Aggressive Behavior in Pediatric Bipolar Disorder - Simonetti, Alessio; Kurian, Sherin; Saxena, Johanna; Verrico, Christopher D.; Restaino, Antonio; Di Nicola, Marco; Soares, Jair C.; Sani, Gabriele; Saxena, Kirti (Frontiers in Psychiatry, 2021)
Background: Impulsive aggression represents a trait marker of pediatric bipolar disorder (PBD). Cortical alterations associated with impulsive aggression and its multiple facets have not being investigated yet in these youth. Aim: To investigate the relationship between cortical thickness and facets of impulsive aggression in youth with PBD. Materials and Methods: Twenty-three youth with PBD and 23 healthy controls (HC) were administered the aggression questionnaire (AQ) and underwent 3T magnetic resonance imaging scan. Cortical thickness was assessed with FreeSurfer. Canonical correlation analyses were used to investigate the relationship between AQ total and subscale scores and cortical thickness in youth with PBD. Results: Youth with PBD had increased scores in the subscales of AQ-anger and AQ-hostility and cortical thinning in areas belonging to the affective network (AN), frontoparietal network (FPN) and cingulo-opercular network (CON) compared to HC. Greater thickness in these networks positively correlated with the AQ-hostility subscale and negatively correlated with AQ-anger subscale. Conclusions: Greater thickness of the AN, FPN and CON might result in greater bias towards negative emotions and greater allocation of attentional resources towards such bias, thus increasing levels of hostility. Also, failure to regulate emotional cues might lead to increased anger outbursts.